CVET in Europe : the way ahead - (:unkn) unknown (Publications Office of the European Union, 2015)
"This publication takes stock of recent Cedefop research on continuing vocational education and training (CVET). It analyses how CVET contributes to reaching economic and social policy objectives of the European Union regarding inclusion, employment, innovation, productivity, competitiveness and growth. CVET is approached as a multidimensional, multistakeholder and multilevel interface between learning and the labour market. The analysis outlines recent achievements in practices and policies of work-based learning, guidance, validation and quality. The publication also highlights gaps and challenges for future CVET policies, in particular improving information and guidance, making participation easier for learners and small enterprises, securing validation mechanisms, and reinforcing quality and monitoring." (Editor, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; I 2.2 Europa; Berufliche Weiterbildung; Weiterbildungspolitik; Lernen am Arbeitsplatz; Bildungsberatung; Weiterbildungsfinanzierung; Europa